Internet źródłem informacji i wiedzy dla przedsiębiorstw nowych technologii - Pondel, Maciej (Internet as a Source of Information and Knowledge for New Technology Enterprises, 2005)
The category of high-tech enterprise appeared at the end of 20 century. It’s importance improves with a development of Internet and internet technologies. Global network has become an essence for many enterprises activity. Efficient usage of Internet, creating new solutions for internet requires knowledge related to marketing, management and also technical knowledge. That is why there is a great necessity to posses the best information and knowledge sources. They are essential to manage projects in efficient way. Internet is one of the most developed and flexible sources. It includes a lot of tools and methods of acquiring knowledge and it became a primal place to search for information and knowledge concerning technology. The main target of this paper it to characterize processes of acquirement technical information and knowledge from Internet.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 217-226